Neutrophil-to-lymphocyte ratio: A biomarker for predicting systemic involvement in iga vasculitis - Rintu Merin George; Arun C Inamadar; Ajit B Janagond (Indian Journal of Rheumatology)
Context:“IgA vasculitis, is an immune complex mediated, self limited cutaneous small vessel vasculitis, characterized by palpable purpurae, arthralgia or arthritis, gastrointestinal and/or renal involvement.” Systemic involvement is considered to be the presence of gastrointestinal (GI) and/or renal involvement in IgA vasculitis patients. Neutrophil-to-lymphocyte ratio (NLR) is a relatively cost-effective and easily obtainable laboratory parameter integrating information on two immune pathways to provide a superior predictive ability over other inflammatory parameters regarding systemic involvement. Aims: The aim of the study was to assess the predictive value of NLR with regard to the systemic involvement in IgA vasculitis. Subjects and Methods: This was a hospital-based cross-sectional study of patients diagnosed with IgA vasculitis, irrespective of age, between 2017 and 2019. Results: The study consisted of 33 patients with a mean age of 33.52 ± 19.78 years. Joint involvement was observed in 52% (17), whereas systemic manifestations in the form of renal involvement were present in 7 (21%), GI in 19 (57.6%), and renal and/or GI in 22 (66.7%) patients. NLR was found to be significantly associated with GI manifestations (P < 0.001). Optimal cutoff value of NLR for predicting systemic involvement was 3.25, with a specificity of 100% and sensitivity of 59%. Conclusions: NLR can be considered as a biomarker for predicting systemic involvement in IgA vasculitis, presenting with only cutaneous with/without joint manifestations.